Dentistry in Brazil: Its history and current trends - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Diniz, Diego Garcia [UNESP] (My University, 2009)
The objectives of this article are to provide a short history of dentistry and dental education in Brazil and to analyze the nature of its development to date. The databases consulted are those provided by the Brazilian Federal Council of Dentistry, Brazilian Ministry of Health, Brazilian Ministry of Education, National Institute of Studies and Educational Research Anísio Teixeira, and Brazilian Institute of Geography and Statistics. Formal dental education in Brazil started in the late nineteenth century with the creation of courses annexed to existing schools of medicine in Rio de Janeiro and Bahia. Today, there are 191 institutions of higher education nationwide granting degrees in dentistry (137 private [71.7 percent] and fifty-four public [28.3 percent]), with a total of 17,157 student positions offered annually. These schools graduate around 10,000 professionals per year - one of the highest rates in the world. Both the distribution of schools of dentistry and of dentists varies among the regions of the country, with the greatest concentrations in major metropolitan centers with high population density, resulting in limited coverage in the more deprived regions. A review of epidemiological data for oral health and distribution of dentists in Brazil indicates that there is a lack of systematic planning for the allocation of the dental workforce and a lack of consideration of regional needs in the development of dental training programs in Brazil today.
Keywords: Brazil; Dental education; Dentist; Labor market; Schools of dentistry